Update of the stability of drugs cytostatic drugs by applying the methodology of the matrix of risk for the manufacture of sterile drugs - Ángela Usarralde-Pérez; Piedad Toro-Chico; Montserrat Pérez-Encinas (Elsevier, 2016)
Objective: To establish limits of validity to opened or reconstituted vials and cytostatic mixtures according to their physico- chemical stability and the level of risk and preparation requirements. The level of risk and preparation requirements were assigned by the risk matrix the Guide of Good Practice of Preparation of Drugs in Hospital Pharmacy Services. Method: A table of stabilities of cytostatic drugs was developed. Physicochemical stability data were obtained from data sheets and literature reviews. The level of risk was assigned by the matrix of risk depending on the requirements of each preparation. When the physico-chemical stability was equal to or higher than indicated by the matrix, it is assumed the terms of validity of the matrix; otherwise, validity periods coincided with the peak period of physicochemical stability. Results: 61 drugs were reviewed. It was assumed the chemical term of validity in 45.9% of opened/reconstituted vials and 50.8% of cytostatic mixtures, and indicated by the risk in the rest array, respectively. According to the matrix, the level of risk was medium in most of cytostatic drugs. Only one preparation was high risk. No preparation obtained low-risk. Conclusions: To assign the term of validity of opened/reconstituted vials and cytostatic mixtures not only it is necessary to consider physical and chemical stability. The level of risk and preparation requirements are also important, allowing more adequate validity periods